Understanding the identity of lived experience researchers and providers: a conceptual framework and systematic narrative review - Gupta, Veenu; Eames, Catrin; Golding, Laura; Greenhill, Beth; Qi, Robert; Allan, Stephanie; Bryant, Alison; Fisher, Peter (Research involvement and engagement, 2023)
Identity is how we understand ourselves and others through the roles or social groups we occupy. This review focuses on lived experience researchers and providers and the impact of these roles on identity. Lived experience researchers and providers use their lived experience of mental or physical disability either as experts by experience, researchers, peer workers, or mental health professionals with lived experience. They must navigate both professional and personal aspects to their roles which can be complex. Performing roles simultaneously embodying professional and lived experiences contribute towards a lack of clarity to identity. This is not adequately explained by the theoretical evidence base for identity. This systematic review and narrative synthesis aimed to provide a conceptual framework to understand how identity of lived experience researchers and providers is conceptualised. A search strategy was entered into EBSCO to access Academic search complete, CINAHL, MEDLINE, PsycINFO, Psych Articles, and Connected papers. Out of the 2049 yielded papers, thirteen qualitative papers were eligible and synthesised, resulting in a conceptual framework. Five themes explained identity positions: Professional, Service user, Integrated, Unintegrated and Liminal. The EMERGES framework, an original conception of this review, found themes of: Enablers and Empowerment, Motivation, Empathy of the self and others, Recovery model and medical model, Growth and transformation, Exclusion and Survivor roots contributed to lived experience researcher and provider identities. The EMERGES framework offers a novel way to understand the identities of lived experience researchers and providers, helping support effective team working in mental health, education, and research settings.